Response of Vitis vinifera L. cv. Sauvignon blanc to Irrigation Strategy and Trellis System in the Semi-Arid Breede River Valley Region: Vegetative Growth, Yield and Juice Characteristics: Effect of Irrigation Strategy and Trellis System on Sauvignon blanc - Howell, Carolyn (South African Journal of Enology and Viticulture, 2026)
Sauvignon blanc is South Africa’s most popular wine for export. Forty percent of the wine grape vineyards in the Breede River Valley are Sauvignon blanc. Since rainfall in the region is low, vineyards depend on irrigation. Therefore, the sensitivity of Sauvignon blanc/99R to water deficits was studied in a field trial from 1998/99 until 2000/01. Producing more grapes with the same volume of irrigation water was also investigated. Irrigation strategies entailed combinations of 50% readily available water (RAW) depletion, 75% RAW depletion and no irrigation between various phenological stages. Irrigation applied at 50% RAW depletion from budbreak in September until harvest was regarded as the control. Each experimental plot was split into a six-strand vertical hedge and a two-tier vertical trellis. Cane mass on the two-tier trellis was lower compared to the six-strand hedge. Irrigation at 75% RAW depletion level until harvest reduced cane mass compared to more frequent irrigation. Drier soil conditions reduced berry mass. Sustained water deficits reduced yield. Substantially more Sauvignon blanc grapes were produced on the two-tier vertical trellis compared to the six-strand hedge with the same amount of irrigation, thereby reducing the blue water footprint and increasing irrigation water use efficiency.